Water vapor line profile at 183-GHz: Temperature dependence of broadening, shifting, and speed-dependent shape parameters. (March 2021) - Koshelev, M.A.; Vilkov, I.N.; Makarov, D.S.; Tretyakov, M.Yu.; Vispoel, B.; Gamache, R.R.; Cimini, D.; Romano, F.; Rosenkranz, P.W.
Highlights: First measurement of SD ЫВ broadening and shifting of the 183-GHz water line for self- and air-broadening, and their temperature dependences. MCRB calculations of the line shape parameters, their temperature and speed-dependence over the range of 200–3000 K agree with measurements. The impact of the updated spectroscopic parameters on radiative-transfer calculations and atmospheric water-vapor retrievals is calculated. Consideration of speed-dependence is necessary for accurate atmospheric water vapor profile retrieval with the 183-GHz line. Abstract: The water vapor line at 183 GHz was studied over the temperature range of 219–358 K using a spectrometer with radioacoustic detection of absorption, providing a signal-to-noise ratio of up to 8000. The study includes the first measurement of speed-dependent collisional broadening and shifting of this line for both self- and air-broadening, and their temperature dependences. The sign of self-shifting changes at about 280 K. Line-shape parameters are obtained for Voigt and quadratic speed-dependent Voigt shape factors. Temperature dependences of the line parameters are analyzed using empirical models from the literature. Theoretical Modified Complex Robert–Bonamy calculations of the line shape parameters, their temperature and speed-dependence are made over the temperature range of 200–3000 K. The measurements and calculations show very good agreement, although with some discrepancies for line shift parameters. The impact of the newly-measured line parameters on atmospheric water-vapor estimation from ground-based and satellite instruments is evaluated by simulation of downwelling and upwelling brightness temperatures and retrieved water-vapor mixing ratio, for atmospheric conditions typical of six climate zones. For the case of ground-based or limb-scanning radiometry with a background of cold space, the impact of speed-dependence is comparable to or exceeds that of measurement error and will introduce systematic errors if neglected. Therefore, consideration of speed-dependence is necessary for accurate estimation of water vapor with this line. The impact on upwelling brightness temperature is smaller.